The roles of microalgae and bacteria in wastewater treatment - Tran Dinh, Nguyen; Phuong Thu, Le; Thanh Dat, Ngo; Khanh Toan, Nguyen; Le Anh, Pham (Vietnam Journal of Biotechnology, 2022)
Nature-based wastewater treatment employing microalgae and bacteria has gained serious attention due to its combination with valuable biomass production. In wastewater, microalgae serves as the primary source of dissolved oxygen (DO) production for bacterial organic matter degradation. In addition, microalgae can effectively remove nutrients, pathogens as well as various heavy metals. Bacteria, on the other hand, has been widely applied in biological wastewater treatment for stabilization of organic matter, nitrification, denitrification, and under some specific conditions, enhanced biological phosphorus removal. When cultured together, microalgae and bacteria can cooperate effectively for wastewater treatment as well as form big flocs which can be harvested easily via sedimentation. However, some natural antagonistic interactions between them should be expected. Various environmental and operational factors showed significant influences on microalgae and bacteria in wastewater. They can impact system performance individually or in combination with others. Therefore, those factors should be carefully monitored for improving performance of the system.